Rice carotenoid biofortification and yield improvement conferred by endosperm-specific overexpression of OsGLK1 - Li, Zhenjun; Gao, Jianjie; Wang, Bo; Xu, Jing; Fu, Xiaoyan; Han, Hongjuan; Wang, Lijuan; Zhang, Wenhui; Deng, Yongdong; Wang, Yu; Gong, Zehao; Tian, Yongsheng; et al. (Frontiers in Plant Science, 2022)
Carotenoids, indispensable isoprenoid phytonutrients, are synthesized in plastids and are known to be deficient in rice endosperm. Many studies, involving transgenic manipulations of carotenoid biosynthetic genes, have been performed to obtain carotenoid-enriched rice grains. Nuclear-encoded GOLDEN2-LIKE (GLK) transcription factors play important roles in the regulation of plastid and thylakoid grana development. Here we show that endosperm-specific overexpression of rice GLK1 gene (OsGLK1) leads to enhanced carotenoid production, increased grain yield, but deteriorated grain quality in rice. Subsequently, we performed the bioengineering of carotenoids biosynthesis in rice endosperm by introducing other three carotenogenic genes, tHMG1, ZmPSY1, and PaCrtI, which encode the enzymes truncated 3-hydroxy-3-methylglutaryl-CoA reductase, phytoene synthase, and phytoene desaturase, respectively. Transgenic overexpression of all four genes (OsGLK1, tHMG1, ZmPSY1, and PaCrtI) driven by rice endosperm-specific promoter GluB-1 established a mini carotenoid biosynthetic pathway in the endosperm and exerted a roughly multiplicative effect on the carotenoid accumulation as compared with the overexpression of only three genes (tHMG1, ZmPSY1, and PaCrtI). In addition, the yield enhancement and quality reduction traits were also present in the transgenic rice overexpressing the selected four genes. Our results revealed that OsGLK1 confers favorable characters in rice endosperm and could help to refine strategies for the carotenoid and other plastid-synthesized micronutrient fortification in bioengineered plants.